Pelatihan Manajemen Pakan Ikan untuk Meningkatkan Produktivitas Kelompok Mina Depok Pancasan Ajibarang - Ananda Bayu Prasetya; Khefit Yulistio; Fadjriatul Rizqoh; Safa Aliya; Muhammad Ulinnuha; Alfina Fajriani; Gatot Sukma Aji; Lupita Dya Ristika; Nabila Syahrika Nugrahaeni; Fadzilah Khoirotun Rizqa; Naufal Okta Brilianto; Nunik Angelia (FKIP Universitas Mataram, 2026)
Feed management is a critical factor influencing the productivity of freshwater aquaculture, particularly among small scale fish farmers who still rely on traditional feeding practices. The Mina Depok Fish Farming Group in Pancasan Village faces challenges related to unmeasured fee efficiency and declining water quality. This community service program aimed to improve the knowledge and skills of fish farmers in feed management through the application of probiotics. The program employed an educational and participatory approach, consisting of activity coordination, oral presentation and interactive discussion, hand-on training in feed management, and qualitative descriptive evaluation. The result demonstrated improve participants’ understanding and changes in farming practices, including accurate feed ration calculation, proper mixing of probiotics with feed and implementation of more systematic feeding practices. These finding indicate that field-based practical training is effective in enhancing fish feed management and supporting the sustainability of community based freshwater aquaculture.